Ultrasound-responsive conductive composite hydrogel and application thereof in myocardial infarction treatment

CN122665183BActive Publication Date: 2026-10-23SOUTHERN MEDICAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611131397.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23
Estimated Expiration
2046-07-29

AI Technical Summary

Technical Problem

(1)功能单一、协同性不足:现有修复材料大多功能较为单一,仅可实现机械支撑、导电改性、药物缓释等单一治疗作用,无法同步兼顾抗氧化、抑制心肌细胞铁死亡、重建心肌电传导以及精准控释药物等多重治疗需求,难以形成协同修复效应,综合治疗效果有限

Benefits of technology

本发明公开了一种兼具pH响应释放、植入后低强度治疗超声按需释放和导电修复功能的智能水凝胶材料。其制备方法为:首先通过高碘酸钠氧化透明质酸引入活性醛基,再利用抗坏血酸还原亚硒酸钠原位制备OHA-SeNPs;随后将OHA-SeNPs、CS、GelMA、GO及光引发剂复配得到复合生物墨水,并采用DLP光固化打印制备导电心肌补片。本发明的治疗逻辑为:偏酸性微环境促进动态席夫碱网络疏松并实现OHA-SeNPs持续释放;补片贴敷并固定于梗死区域心外膜表面后,再向补片对应区域施加低强度治疗超声,可进一步触发OHA-SeNPs按需释放。含硒纳米颗粒则抑制心肌细胞脂质过氧化和铁死亡,GO导电网络改善损伤区域电信号传导,二者共同实现心肌梗死后的细胞保护与电微环境重建。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122665183B_ABST
    Figure CN122665183B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of biomedical engineering and tissue engineering materials, and particularly relates to an ultrasound-responsive conductive composite hydrogel and application thereof in myocardial infarction treatment. The composite hydrogel provided by the application comprises oxidized hyaluronic acid modified selenium nanoparticles, chitosan, methacrylated gelatin, graphene oxide and a photoinitiator, and is formed by digital light processing printing. The material can realize controllable loosening of the hydrogel network and continuous release of the selenium-containing nanoparticles in the acidic microenvironment after myocardial infarction, and can further enhance the on-demand release of the selenium-containing nanoparticles under low-intensity therapeutic ultrasound stimulation; the released selenium-containing nanoparticles are used for supplementing local selenium-related antioxidant defense, inhibiting lipid peroxidation and ferroptosis, and the conductive network of the graphene oxide can be used for improving the electrical signal conduction of the damaged area, thereby synergistically promoting the repair of myocardial structure, cell electrical coupling and cardiac function after myocardial infarction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical engineering and tissue engineering materials technology, specifically relating to an ultrasound-responsive conductive composite hydrogel and its application in the treatment of myocardial infarction. Background Technology

[0002] Following a myocardial infarction, the damaged myocardial cells experience a strong oxidative stress response due to ischemia and hypoxia, leading to ferroptosis and significant loss of myocardial cells. Simultaneously, the fibrous scar tissue formed in the infarcted area lacks electrical conductivity, disrupting normal cardiac electrical signal conduction pathways and ultimately causing a series of secondary problems such as arrhythmias and cardiac dysfunction. Currently, repair materials used in the treatment of myocardial infarction still have many technical shortcomings, specifically as follows: (1) Single function and insufficient synergy: Most existing repair materials have relatively single functions, and can only achieve single therapeutic effects such as mechanical support, conductive modification, and drug sustained release. They cannot simultaneously meet multiple therapeutic needs such as anti-oxidation, inhibition of myocardial cell iron death, reconstruction of myocardial electrical conduction, and precise controlled release of drugs, making it difficult to form a synergistic repair effect and resulting in limited comprehensive therapeutic effects.

[0003] (2) Poor spatiotemporal control of drug delivery: Traditional drug carriers (microspheres, liposomes, etc.) mainly rely on passive diffusion or simple pH environment response to release drugs, which cannot adapt to the dynamic evolution of the pathological process after myocardial infarction. In response to the differentiated treatment needs of different pathological stages such as the burst of reactive oxygen species in the acute phase of infarction and myocardial electrical remodeling in the chronic phase, such carriers are difficult to achieve on-demand, pulsed precise drug delivery, and the spatiotemporal control of drug delivery is insufficient.

[0004] (3) Weak biointegration and insufficient targeting and anchoring ability: Most repair materials rely only on physical filling and weak interaction to attach to the myocardial injury site, which easily leads to problems such as material displacement and premature removal; at the same time, the materials lack the ability to actively target the damaged myocardium, making it difficult to stably act on the lesion area, and the long-term treatment effect is difficult to guarantee.

[0005] (4) The bioactivity and compatibility of materials need to be improved: Some synthetic conductive materials (such as pure polypyrrole) and unmodified carbon-based materials (such as carbon nanotubes) are prone to inducing persistent inflammatory reactions after being implanted into the body, and have biocompatibility defects, which are not conducive to the long-term repair of damaged myocardial tissue.

[0006] Among various myocardial repair materials, hydrogels have become an ideal therapeutic carrier for myocardial infarction due to their excellent biomimetic properties. Their three-dimensional porous structure is similar to the extracellular matrix of myocardium, providing mechanical support for damaged myocardium, relieving ventricular wall stress, and delaying adverse ventricular remodeling. Simultaneously, hydrogels are highly modifiable, have high drug loading capacity, and exhibit controllable degradation. After functional modification, they can possess pH-responsive release, tissue adhesion, and electrical conductivity. For myocardial infarction repair, simply constructing exogenous conductive pathways is insufficient to fully restore the electrical microenvironment of damaged myocardium; it is also necessary to simultaneously protect the antioxidant and electrical coupling basis of surviving myocardial cells in the infarct border zone.

[0007] In summary, current materials for myocardial infarction repair still face significant technological bottlenecks. However, intelligent hydrogels possess the potential for multi-functional integration and are an excellent carrier for overcoming existing treatment limitations. Therefore, there is an urgent need to develop a multifunctional intelligent hydrogel treatment system for myocardial infarction that integrates active targeting, intelligent anchoring, on-demand drug release, and conductive repair to meet the multi-stage, synergistic repair treatment needs of myocardial infarction. Summary of the Invention

[0008] To overcome the shortcomings of the prior art, this invention provides a composite hydrogel material that combines pH-responsive release, on-demand release with low-intensity therapeutic ultrasound, and conductive repair properties. This material is composed of OHA-SeNPs, CS, GelMA, and GO: OHA-SeNPs provide a selenium source and inhibit lipid peroxidation and ferroptosis; CS forms dynamic Schiff base bonds with OHA aldehyde groups to impart pH responsiveness and network tunability; GelMA is used for photocrosslinking and printing; and GO is used to construct a conductive network and improve electrical signal conduction. The core logic of this system lies in simultaneously protecting the damaged cellular electrophysiological basis after myocardial infarction and reconstructing the exogenous conductive microenvironment, thereby achieving synergistic therapy of anti-ferroptosis protection and electrical microenvironment reconstruction.

[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing an ultrasonically responsive conductive composite hydrogel, the method comprising the following steps: S1. Preparation of oxidized hyaluronic acid modified selenium nanoparticles (OHA-SeNPs):

[0010] S11. Dissolve sodium hyaluronate (NaHA) in water, and add sodium periodate (NaIO4) solution under light-proof ice bath conditions to carry out an oxidative modification reaction; after the reaction is completed, the resulting reaction solution is dialyzed and dried to obtain oxidized hyaluronic acid (OHA) with active aldehyde groups. S12. Dissolve oxidized hyaluronic acid (OHA) in water, add sodium selenite (Na2SeO3) solution, and then add ascorbic acid (Vc) solution under stirring conditions. Selenium nanoparticles (SeNPs) are generated in situ by reduction reaction. After the solution turns orange-red and the color stabilizes, it is purified by ultrafiltration to obtain OHA-SeNPs dispersion. The key to this step is to introduce reactive aldehyde groups onto the HA backbone through sodium periodate oxidation, and to use OHA as both a stabilizer and a functional molecule to synthesize selenium nanoparticles with both CD44 receptor targeting and aldehyde group reactivity in one step.

[0011] S2. Dissolve chitosan CS in an acetic acid solution with a mass fraction of 0.5-2 vol% to prepare a CS solution with a mass fraction of 1%-3%. S3. Add methacrylamide gelatin (GelMA), graphene oxide (GO), and photoinitiator to phosphate-buffered saline (PBS), disperse evenly, and prepare a premix solution. S4. The OHA-SeNPs dispersion from S1, the CS solution from S2, and the premixed solution from S3 are mixed at 4-10℃ under light-protected conditions to obtain a composite bio-ink. Finally, it is printed using digital light processing (DLP) technology. The mixing of OHA-SeNPs and CS allows the aldehyde and amino groups to pre-form dynamic Schiff base bonds, giving the system excellent printability and self-healing properties.

[0012] Preferably, the sodium hyaluronate in S11 has a molecular weight of 300-500 kDa, more preferably about 400 kDa.

[0013] Preferably, the mass ratio of sodium hyaluronate to sodium periodate (NaIO4) is 100:10-50, more preferably 100:20-25.

[0014] Preferably, in S11, the oxidation modification reaction takes 2-6 hours.

[0015] Preferably, in S12, the ratio of oxidized hyaluronic acid to sodium selenite is 150-250g:1mol, and the molar ratio of ascorbic acid to selenium in sodium selenite is ≥4.

[0016] Preferably, in S11, the dialysis is performed by placing the dialysis solution in a dialysis bag with a molecular weight cutoff of 3-4 kDa and dialyzing with ultrapure water at 4°C for 70-80 hours, with the dialysis solution being replaced every 7-9 hours.

[0017] Preferably, in S12, the dialysis involves transferring the reaction solution into an ultrafiltration centrifuge tube with a molecular weight cutoff of 9-11 kDa, centrifuging at 4000 rpm to concentrate the solution, and washing it with water multiple times to remove residual ions and free small molecule impurities.

[0018] Preferably, the degree of deacetylation of the chitosan in S2 is ≥90%.

[0019] Preferably, the substitution rate of the methacrylamide gelatin in S3 is 60%-90%, the monolayer rate of the graphene oxide is >95%, the lateral dimension is 5-8 μm, and the pH of the phosphate buffer is 7.0-7.5.

[0020] Preferably, the photoinitiator in S4 includes 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylphenylacetone (Irgacure 2959) and lithium phenylbis(2,4,6-trimethylbenzoyl)phosphate (LAP).

[0021] Preferably, in step S4, the volume ratio of the OHA-SeNPs dispersion, CS solution, and premix is ​​2:1:2; the final concentration of the OHA-SeNPs, based on the final composite bio-ink, is 25-100 μg / mL, preferably 51.4 μg / mL; the final concentration of the photoinitiator is 0.1%-0.5% w / v, preferably 0.25% w / v; the mass-volume concentration of the GelMA is 6%-10%, preferably 8%; and the mass-volume concentration of the GO is 0.5-2.0 mg / mL, preferably 1.0 mg / mL.

[0022] The second aspect of the present invention also provides an ultrasonically responsive conductive composite hydrogel prepared by the preparation method described in the first aspect.

[0023] The third aspect of the present invention also provides the application of the ultrasound-responsive conductive composite hydrogel described in the second aspect in the preparation of myocardial infarction repair materials, wherein the myocardial infarction repair materials include myocardial patches for the treatment of myocardial infarction.

[0024] Preferably, after the myocardial infarction repair material is applied and fixed to the epicardial surface of the infarct area, low-intensity therapeutic ultrasound is applied to the corresponding area of ​​the myocardial infarction repair material to trigger the on-demand release of OHA-SeNPs in the myocardial infarction repair material; The low-intensity therapeutic ultrasound can be applied directly to the patch area on the cardiac surface during surgery via a sterile coupling medium, or applied to the corresponding patch area via the precordial surface after surgery, depending on experimental or clinical operating conditions. This invention does not require pre-implantation external treatment of the patch as a necessary step; ultrasound treatment is used as an external trigger signal after patch application.

[0025] The ultrasound-responsive conductive composite hydrogel described above is used to treat myocardial infarction and has dual intelligent response and synergistic therapeutic effects. Its mechanism of action is explained below: (1) pH-responsive network loosening and background release: Local lactic acid accumulation after myocardial infarction can form a slightly acidic microenvironment. Under this environment, the amino group of CS is protonated, and the dynamic Schiff base bond (-C=N-) between OHA-SeNPs and CS undergoes reversible hydrolysis, which loosens the hydrogel network to promote the continuous release of OHA-SeNPs, thereby supplementing local selenium-related antioxidant defense and counteracting long-term lipid peroxidation damage.

[0026] (2) Tissue adhesion and stable residence: The GelMA photocrosslinking network provides basic morphological stability. The OHA / CS dynamic network can form multi-point interactions with amino, hydroxyl and other groups on the tissue surface, so that the hydrogel patch can maintain good adhesion to the epicardial injury area and reduce the risk of material displacement.

[0027] (3) Low-intensity therapeutic ultrasound-triggered on-demand release: After the hydrogel patch is applied and stably resides on the epicardial surface of the infarct area, low-intensity therapeutic ultrasound can be applied to the corresponding area of ​​the patch according to treatment needs. The mechanical vibration, microflow and cavitation-related effects generated by ultrasound can temporarily disturb the dynamic Schiff base network and porous structure, thereby enhancing the release of OHA-SeNPs from the applied patch; this triggering process no longer depends on the single factor of in vivo pH, nor does it require pretreatment of the patch before implantation, which is conducive to realizing on-demand release regulated by exogenous physical commands after implantation.

[0028] (4) Multifunctional synergy: After being taken up by cells, the released OHA-SeNPs can serve as a selenium source to enhance selenium-related antioxidant defenses such as GPX4 and TXNRD1, inhibit lipid peroxidation, abnormal accumulation of ferrous ions and ferroptosis; at the same time, the uniformly dispersed GO network in the hydrogel provides conductive bridging, improves electrical signal transduction in the infarct area and promotes the recovery of CX43-related electrical coupling.

[0029] More preferably, the low-intensity therapeutic ultrasound has a frequency of 1.0-3.0 MHz and an intensity of 0.5-1.5 W / cm². 2 The single treatment time is 1-5 minutes, and a total of 10-20 treatments are performed, with an interval of 20-30 hours between adjacent treatments; the preferred frequency is 1.0 MHz and the intensity is 1.0 W / cm². 2 Each treatment takes 3 minutes, and a total of 14 treatments are performed, with a 24-hour interval between two consecutive treatments.

[0030] Preferably, the myocardial patch uses the ultrasound-responsive conductive composite hydrogel as its core functional matrix and may further include medically acceptable excipients, including but not limited to biocompatible solvents, buffer regulators, thickeners and stabilizers, shaping agents, antibacterial excipients, and sustained-release carrier excipients. These excipients can effectively optimize the molding properties, rheological properties, adhesion properties, and in vivo degradation properties of the repair material, improving the material's compatibility with myocardial tissue, biocompatibility, and clinical safety. This allows the repair material to act stably on the myocardial infarction injury area, assisting in myocardial cell proliferation, repairing damaged myocardial tissue, and improving myocardial electrophysiological function, making it suitable for tissue repair and cardiac function reconstruction in acute and subacute myocardial infarction.

[0031] Compared with the prior art, the beneficial effects of the present invention are: This invention discloses a smart hydrogel material that combines pH-responsive release, on-demand release of low-intensity therapeutic ultrasound after implantation, and conductive repair functions. The preparation method is as follows: firstly, active aldehyde groups are introduced by oxidizing hyaluronic acid with sodium periodate, and then OHA-SeNPs are prepared in situ by reducing sodium selenite with ascorbic acid; subsequently, OHA-SeNPs, CS, GelMA, GO, and a photoinitiator are compounded to obtain a composite bio-ink, and conductive myocardial patches are prepared using DLP photopolymerization printing. The therapeutic logic of this invention is as follows: the slightly acidic microenvironment promotes the loosening of the dynamic Schiff base network and achieves continuous release of OHA-SeNPs; after the patch is applied and fixed to the epicardial surface of the infarcted area, low-intensity therapeutic ultrasound is applied to the corresponding area of ​​the patch, which can further trigger the on-demand release of OHA-SeNPs. Selenium-containing nanoparticles inhibit lipid peroxidation and ferroptosis in cardiomyocytes, and the GO conductive network improves electrical signal conduction in the damaged area; together, they achieve cell protection and electrical microenvironment reconstruction after myocardial infarction.

[0032] Specifically, the present invention has the following advantages: (1) Intelligent delivery of “microenvironment response + external physical triggering after implantation”: combining pathological microenvironment signals (pH) with external physical commands (low-intensity therapeutic ultrasound) to achieve the delivery logic of “maintaining release in acidic environment background” and “enhancing release by ultrasound command after patch application”, thus solving the problem of the unadjustable release rhythm of traditional carriers.

[0033] (2) Long-term and stable tissue integration: Through the aldehyde-amino covalent bonding mechanism, the hydrogel is chemically anchored to myocardial tissue, which far exceeds the physical adsorption of traditional materials, ensuring the long-term residence and stable function of the treatment platform.

[0034] (3) Multi-mechanism synergistic treatment: The single system integrates the ferroptosis inhibition mechanism of OHA-SeNPs, the myocardial electrical conduction remodeling effect of GO, the pH response and tissue adhesion of the dynamic network of oxidized hyaluronic acid (OHA) / chitosan (CS), and the cell affinity and photocuring advantages of GelMA, and promotes cardiac function repair from multiple dimensions of anti-lipid peroxidation, myocardial electrophysiological repair and bioadaptation integration.

[0035] (4) Excellent biocompatibility and targeting: Based on natural derivatives such as hyaluronic acid, chitosan, and gelatin, it has good biocompatibility. Utilizing the natural targeting of HA to the highly expressed CD44 receptor in the damaged area, the precision and efficiency of treatment are improved.

[0036] (5) High clinical translation potential: This hydrogel system is composed of common biomaterials such as hyaluronic acid, chitosan, gelatin derivatives and carbon-based conductive fillers; low-intensity therapeutic ultrasound is used as an external trigger after patch implantation, which has the advantages of convenient operation and controllable parameters. In addition, it can be made into a myocardial patch and its shape can be customized by preoperative DLP printing. Implantation can be completed by applying it during the operation. After implantation, ultrasound triggering release can be applied as needed, which has the potential for further translation and development. Attached Figure Description

[0037] Figure 1 Scanning electron microscope images of the lyophilized sections of four groups of hydrogels: SeG, GG, SeGG, and SeGGU.

[0038] Figure 2 The images show the microstructure and particle size distribution of OHA-SeNPs, where A is the microstructure of OHA-SeNPs observed using a scanning electron microscope, and B is the particle size distribution of OHA-SeNPs measured using dynamic light scattering.

[0039] Figure 3 High-resolution XPS spectra of C 1s (A), N 1s (B), and O 1s (C) for SeG, GG, and SeGG hydrogels, and high-resolution XPS spectra of Se 3d (D) for SeG and SeGG hydrogels.

[0040] Figure 4 Fourier transform infrared spectra of four groups of hydrogels: SeG, GG, SeGG, and SeGGU.

[0041] Figure 5 The graphs show the GelMA concentration screening and the compressive mechanical properties of each group of hydrogels. A represents the compressive stress-strain curves and compressive modulus of 6%, 8%, and 10% GelMA hydrogels, while B represents the compressive stress-strain curves and compressive modulus of SeG, GG, SeGG, and SeGGU hydrogels.

[0042] Figure 6 The storage modulus G′ and loss modulus G″ curves of SeG, GG, SeGG and SeGGU hydrogels under frequency scanning conditions are shown.

[0043] Figure 7 Cyclic voltammetry curves and volumetric conductivity quantification plots are shown for SeGG hydrogels with final GO concentrations of 0.5, 1.0, and 2.0 mg / mL, and for SeGGU hydrogels with a final GO concentration of 1.0 mg / mL.

[0044] Figure 8 The graphs show the swelling ratio and mass retention rate of SeG, GG, SeGG, and SeGGU hydrogels over time, with the left graph representing the swelling ratio and the right graph representing the mass retention rate.

[0045] Figure 9 The graphs show the swelling ratio and mass retention of SeGGU hydrogel over time at pH 7.4 and pH 5.6, with the left graph representing the swelling ratio and the right graph representing the mass retention.

[0046] Figure 10 The figures show the in vitro cumulative release curves of selenium in hydrogels. The left figure shows the release behavior of three groups: SeG, SeGG, and SeGGU. The right figure shows the release behavior of SeGGU under pH 7.4 and pH 5.6 conditions.

[0047] Figure 11 Immunofluorescence staining images of α-actinin and CX43 in primary cardiomyocytes from Control, Hypoxia, and different hydrogel intervention groups, and quantitative images of CX43-positive area.

[0048] Figure 12 Images of calcium transient fluorescence, calcium oscillation curves, and quantitative graphs of the number of calcium peaks within 10 s for cardiomyocytes in the Hypoxia, Hypoxia-SeG, Hypoxia-GG, Hypoxia-SeGG, and Hypoxia-SeGGU groups.

[0049] Figure 13 M-mode echocardiography and quantitative analysis of LVEF, LVFS, LVIDd, LVIDs and corresponding changes in rats in the Sham, MI, SeG, SeGG and SeGGU groups at 1 week and 4 weeks post-surgery.

[0050] Figure 14 HE staining, Masson trichrome staining, and quantitative graphs of infarct wall thickness and infarct area percentage were performed on the heart tissues of rats in the Sham, MI, SeG, SeGG, and SeGGU groups. Detailed Implementation

[0051] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0052] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0053] Example 1: Preparation of smart hydrogel (OHA-SeNPs / CS / GelMA / GO) 1.1 Synthesis of Oxidized Hyaluronic Acid (OHA): (1) Weigh 100.0 mg of sodium hyaluronate (NaHA, molecular weight approximately 400 kDa, catalog number EFL-HA-400K, EFL, China) into a 50 mL brown light-proof reaction bottle.

[0054] (2) Add 10.0 mL of ultrapure water and stir magnetically until completely dissolved to obtain a 1% (w / v) HA solution.

[0055] (3) Place the reaction flask in an ice-water bath to protect it from light; separately weigh 21.4 mg of sodium periodate (NaIO4, purity ≥99.5%, Aladdin), dissolve it in 1 mL of ultrapure water, and prepare a 0.1 M solution.

[0056] (4) Using a constant flow syringe pump, slowly add the prepared NaIO4 solution to the HA solution at a rate of 0.1 mL / min, while stirring continuously throughout the process.

[0057] (5) After the addition is complete, continue the reaction for 4 hours in an ice-water bath and in the dark.

[0058] (6) After the reaction is complete, add 0.5 mL of ethylene glycol to quench the unreacted sodium periodate and continue stirring for 30 minutes.

[0059] (7) Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 3.5 kDa and dialyze it against ultrapure water at 4°C for 72 hours, changing the water every 8 hours.

[0060] (8) Freeze-dry the dialysate to obtain a white flocculent solid, which is oxidized hyaluronic acid (OHA).

[0061] In this embodiment, the oxidation degree of OHA was controlled by the amount of sodium periodate added, and the aldehyde titration result was not considered as a necessary limitation. Based on the molar ratio of NaIO4 to NaHA repeating units, the oxidation degree of OHA obtained in this embodiment was 40%.

[0062] 1.2 Synthesis and characterization of oxidized hyaluronic acid-selenium nanoparticles (OHA-SeNPs): (1) Weigh 20.0 mg of the prepared OHA and dissolve it in 20 mL of ultrapure water to obtain a 1 mg / mL OHA solution.

[0063] (2) Measure 1.0 mL of 0.1 M sodium selenite (Na2SeO3) aqueous solution and add it to the above OHA solution. Stir magnetically for 30 minutes at room temperature to ensure thorough mixing.

[0064] (3) While stirring vigorously, quickly add 4.0 mL of freshly prepared 0.1 M ascorbic acid aqueous solution. The solution color gradually changes from colorless to light yellow within a few minutes, and finally becomes a stable orange-red.

[0065] (4) Continue stirring the reaction at room temperature in the dark for 6 hours to ensure the reaction is complete.

[0066] (5) Transfer the reaction solution to an ultrafiltration centrifuge tube with a molecular weight cutoff of 10 kDa, centrifuge at 4000 rpm to concentrate, and wash three times with ultrapure water to remove unreacted ions and free small molecules.

[0067] (6) Finally, the volume was adjusted to 10 mL with ultrapure water to obtain the OHA-SeNPs stock solution.

[0068] (7) Microscopic morphology characterization of OHA-SeNPs: 1 ml of OHA-SeNPs stock solution was dropped onto the surface of a clean silicon wafer and allowed to dry naturally at room temperature. After the sample was conductive, the microscopic morphology and dispersion state of OHA-SeNPs were observed using a scanning electron microscope (GeminiSEM 300, Carl Zeiss, Germany), and representative images were acquired.

[0069] (8) Characterization of OHA-SeNPs particle size distribution: Take 1 ml of OHA-SeNPs stock solution, mix thoroughly, and add to a clean particle size detection cell. Determine the hydrated particle size and particle size distribution of OHA-SeNPs using a nanoparticle size and Zeta potential analyzer (Zetasizer Nano ZS90, Malvern Panalytical, UK) at 25 ℃. Each sample was measured in triplicate, and the particle size distribution results are expressed as intensity (%).

[0070] 1.3 Formulation and hydrogel molding of composite bio-ink: (1) GelMA Concentration Screening: To determine the suitable base gel concentration for DLP printing and myocardial patching, 6%, 8%, and 10% (w / v) GelMA hydrogels were prepared and subjected to compression mechanical tests. Considering molding stability, mechanical compatibility, and printability, 8% (w / v) GelMA was finally selected as the base concentration for subsequent composite hydrogels (see [link to product details]). Figure 5 (A in the middle).

[0071] (2) Preparation of chitosan solution: Weigh 15.0 mg chitosan (CS, degree of deacetylation ≥95%, sigma), dissolve it in 1.0 mL of 1% (v / v) glacial acetic acid aqueous solution, vortex and dissolve overnight at 4℃ to obtain 1.5% (w / v) CS solution.

[0072] (3) Preparation of GelMA / GO premix: Methacrylamide gelatin (GelMA, degree of substitution approximately 80%) was weighed and dissolved in PBS (0.01 M, pH 7.4). Photoinitiator LAP was added to achieve a final GelMA / LAP solution with a final concentration of 8% (w / v) and a final LAP concentration of 0.25% (w / v). Simultaneously, monolayer graphene oxide (GO, monolayer content >95%, lateral size 5-8 μm) was dispersed in PBS (0.01 M, pH 7.4), ultrasonically dispersed in an ice bath, and then added to the GelMA / LAP solution to achieve a final GO concentration of 1.0 mg / mL in the final composite bioink. To screen conductivity, composite bioinks with final GO concentrations of 0.5, 1.0, and 2.0 mg / mL were prepared.

[0073] (4) Mixing and cross-linking: The OHA-SeNPs dispersion, CS solution, and GelMA / GO / LAP premix were mixed sequentially at 4°C in the dark, with a volume ratio of 2:1:2. The final concentration of OHA-SeNPs in the final composite bio-ink was controlled to be 51.4 μg / mL. The mixture was vortexed and degassed in the dark to obtain a homogeneous composite bio-ink.

[0074] (5) Using digital light processing (DLP) technology, the aforementioned composite bio-ink is printed into a patch structure adapted to the myocardial infarction area: An appropriate amount of the above ink is used for DLP printing to obtain a disc-shaped or composite hydrogel patch (denoted as SeGG gel) that matches the infarction area. The specific operation is as follows: First, a disc-shaped hydrogel patch model, or a model simulating the morphology of an infarct region, was constructed using 3D modeling software and then sliced ​​within a DLP printing system (Zhuhai Seine 3D, model DLP1.0). Printing parameters were optimized based on the physical properties of the ink; in this embodiment, a light source wavelength of 405 nm, a single-layer exposure time of 20 seconds, and a layer thickness of 50 μm were used. During printing, composite bio-ink was injected into the printer's ink tank, and a preset program was initiated to complete layer-by-layer curing. After printing, the molding support was removed, and the surface was gently rinsed with preheated PBS to remove any uncrosslinked residual ink, ultimately yielding a conductive composite hydrogel patch.

[0075] Example 2: Preparation of Smart Hydrogel (SeGGU) The composition and preparation steps were the same as in Example 1; the difference was the introduction of low-intensity therapeutic ultrasound as an external trigger condition, and the resulting ultrasound intervention group was denoted as SeGGU. In in vitro release or cell experiments, the formed SeGG hydrogel was placed in a PBS release medium or a Transwell culture system and low-intensity therapeutic ultrasound was applied; in in vivo application, the SeGG patch was applied and fixed to the epicardial surface of the infarct area, and then low-intensity therapeutic ultrasound was applied to the corresponding area of ​​the patch. The ultrasound parameters were set as follows for each application: frequency 1.0 MHz, power density 1.0 W / cm². 2 The duration is 3 minutes. SeGGU is the name of the ultrasound intervention group and does not mean that pretreatment is necessary before patch implantation.

[0076] Comparative Example 1: Preparation of Control Hydrogel 1 (No SeNPs, Physically Mixed Sec) The preparation steps were the same as in Example 1, except that OHA-SeNPs were not synthesized in steps 1.1 and 1.2. Instead, selenomethylselenocysteine ​​(Sec) was directly mixed with CS solution and GelMA / GO / LAP premix, and a hydrogel was prepared under the same DLP photocuring conditions to simulate a system with a physically mixed selenium source but lacking the OHA / CS dynamic network. The resulting gel was denoted as SeG gel.

[0077] Comparative Example 2: Preparation of Control Hydrogel 2 (GelMA+GO, without selenium component) When preparing the ink, an equal volume of PBS was used instead of OHA-SeNPs dispersion and CS solution. The GelMA / GO / LAP premix was directly printed into a hydrogel by DLP printing. The resulting hydrogel is denoted as GG hydrogel.

[0078] Experimental Example 1: Physicochemical Properties and Structural Characterization of Hydrogel Materials 1. Exploration of microscopic morphology (SEM) and its network regulation mechanism The cross-section of the freeze-dried hydrogel was observed using scanning electron microscopy (SEM). Figure 1 The results showed that all groups of hydrogel samples (SeG, GG, SeGG, SeGGU) could form interconnected porous structures; the specific analysis is as follows: (1) Synergistic effect of dynamic covalent crosslinking and GO nano-reinforcement on network structure: Compared with the control hydrogel, SeGG exhibits a more continuous pore wall structure and better network integrity. This morphological feature may be related to the combined effects of OHA / CS dynamic Schiff base crosslinking and the reinforcing effect of GO nanosheets.

[0079] 1) Introduction of dynamic covalent bonds: Schiff base bonds formed by the aldehyde groups on the surface of oxidized hyaluronic acid (OHA) and the amino groups on chitosan (CS) and GelMA chains construct a second dynamic network on the basis of the original photocrosslinking network, which significantly improves the crosslinking density.

[0080] 2) Nano-reinforcing effect of GO: Under high-magnification SEM, graphene oxide (GO) sheets are visible as wrinkled, uniformly embedded and overlapping within the gel framework. These nanosheets not only act as nanoscaffolds to enhance the mechanical strength of the pore walls, but their abundant surface functional groups also further bind with polymer chains through hydrogen bonds, making the network structure more compact.

[0081] (2) Distribution and loading of SeNPs: Granular structures are visible on the pore walls and interpore skeleton surface of the SeGG cross-section, combined with the following... Figure 3 The Se 3d high-resolution XPS and Figure 2 The particle size characterization results of OHA-SeNPs suggest that OHA-SeNPs have been introduced into the composite hydrogel network.

[0082] (3) Analysis of the dynamic effects of ultrasound stimulation on network structure: For SeGGU, the introduction of ultrasound has a multi-dimensional regulatory mechanism on the hydrogel network: 1) Cavitation and Microfluidic Effects: The micro-jet flow generated by low-frequency ultrasound in the liquid medium produces instantaneous mechanical shear forces on the hydrogel network. Due to the dynamic reversibility of Schiff base bonds, the mechanical energy of ultrasound can temporarily disrupt the local covalent equilibrium, resulting in a minute instantaneous expansion of the network pore size.

[0083] 2) Structural basis for on-demand release: This controlled loosening of the microstructure explains the stepwise release behavior of SeGGU under ultrasound triggering. When ultrasound stops, the gel network can quickly re-crosslink due to the self-repairing properties of the dynamic bonds, thereby preventing sustained burst release of the drug and achieving precise spatial and temporal controlled release.

[0084] 3) Thermal effect: The local temperature rise generated by ultrasound, although weak, helps to accelerate the thermal motion of molecular chains, and further synergistically accelerates the hydrolysis of dynamic bonds in the acidic microenvironment.

[0085] 2. Analysis of elemental valence state and chemical bonding (XPS & FTIR): (1) XPS analysis: elemental composition and stability of elemental selenium ( Figure 3 The analysis is as follows: 1) Se 3d valence state analysis: After peak fitting, the high-resolution Se 3d spectrum showed Se-related characteristic double peaks at approximately 55.3 eV (3d5 / 2) and 56.0 eV (3d3 / 2), indicating that selenium mainly exists in the form of zero-valent nano-selenium. This result shows that under the stabilizing effect of OHA, sodium selenite can form relatively stable OHA-SeNPs after reduction with ascorbic acid, providing a material basis for subsequent anti-lipid peroxidation and anti-ferroptosis effects.

[0086] 2) Direct evidence of imine bonds: Detailed analysis of the N 1s spectrum revealed a third component besides the amide nitrogen (399.8 eV) and the protonated amino group (401.2 eV)—a characteristic peak at 399.2 eV. This peak is attributed to the imine nitrogen (C=N), which, from the perspective of elemental orbital binding energy, directly confirms that the aldehyde group of OHA underwent a nucleophilic addition reaction with the amino groups on the CS and GelMA molecular chains, successfully constructing a dynamic covalent network.

[0087] (2) FTIR analysis: Cooperative crosslinking between molecular chains ( Figure 4 The analysis is as follows: 1) Evolution of characteristic peaks: In the SeGG composite gel, the amide I band and C=N related absorption peaks overlap and change in shape, suggesting that there are multiple interactions between GelMA, CS and OHA, such as amide structure, Schiff base bond and hydrogen bond.

[0088] 2) Bond displacement and superposition effect: 1633 cm -1 The peak shift and intensity enhancement at this point are the result of the synergistic effect of multiple chemical bonds. On the one hand, the amide I band (C=O stretching vibration) of GelMA contributes to the fundamental intensity; on the other hand, the absorption peak of the newly formed Schiff base bond (C=N) (typically located at 1640 cm⁻¹) is also a contributing factor. -1 The orbital overlap with the amide band (nearby) caused the peak shape to broaden and shift slightly towards lower wavenumbers.

[0089] 3) Hydrogen bond network assisted: at 3200-3500 cm -1In the broad spectral region, the stretching vibration peaks of -OH and -NH become wider and thicker, indicating that in addition to chemical cross-linking, there are also a large number of intermolecular hydrogen bonds between CS, GelMA and OHA. This dual effect of "chemical cross-linking + physical hydrogen bonding" further stabilizes the three-dimensional structure of the hydrogel.

[0090] (3) Discussion on the relationship between chemical bonding and intelligent response mechanism: 1) Chemical basis of pH response characteristics: Schiff base bonds (C=N) exhibit significant pH sensitivity. In the acidic microenvironment (pH 5.5-6.5) of myocardial infarction areas or sites of inflammation, protonation induces reversible hydrolysis of imine bonds. This molecular-level "dissociation" weakens the degree of gel cross-linking, inducing controllable loosening of the three-dimensional network, thus explaining the accelerated release behavior of SeNPs under acidic conditions observed in Experiment Example 2 (see subsequent examples). Figure 10 (The right image in the image).

[0091] 2) Synergistic effect triggered by ultrasound: The variability of dynamic covalent bonds enables the network to undergo instantaneous conformational adjustment when stimulated by external physical fields (such as ultrasonic mechanical shear force), forming a synergy with the acidic environment to achieve high-precision on-demand burst release.

[0092] 3. In-depth exploration of mechanical and rheological properties (1) Compressive mechanical properties: Synergistic effect of dual-network crosslinking and nano-reinforcement ( Figure 5 The analysis is as follows: 1) Structural origin of modulus enhancement: Experimental results show that the compressive modulus of SeGG is higher than that of the SeG group with physically mixed selenium sources, indicating that the GelMA photocrosslinking network and the OHA / CS dynamic Schiff base network constructed inside the composite hydrogel can synergistically improve mechanical stability. The dynamic bonds can undergo reversible breakage and recombination during the stress process, and the GO sheets can also participate in load transfer as nano-reinforcing units, thereby improving the integrity of the patch structure.

[0093] 2) Bridging and dislocation hindering effects of GO: As a nanofiller, GO sheets are uniformly dispersed in the polymer matrix, acting as physical cross-linking centers. GO's abundant high modulus properties and its strong interactions with polymer chains (such as hydrogen bonds and π-π stacking) effectively transfer loads. Under high strain, GO sheets can hinder crack propagation, further enhancing the structural stiffness of SeGG.

[0094] 3) Myocardial biomechanical compatibility: Based on existing myocardial tissue biomechanical range (Pok S, Benavides OM, Hallal P, Jacot JG. Use of Myocardial Matrix in a Chitosan-Based Full-ThicknessHeart Patch. Tissue Engineering Part A. 2014;20:1877–1887. DOI: 10.1089 / ten.tea.2013.0620.) and Figure 5 The compression test results show that the compression modulus of SeGG / SeGGU is in the kPa range suitable for soft tissue application, which can provide local support while avoiding significant rigidity mismatch.

[0095] (2) Rheological behavior: Viscoelastic equilibrium and structural stability Figure 6 The analysis is as follows: 1) Solid-like elastic behavior: In the rheological frequency scan, the storage modulus G′ of SeGG and SeGGU is generally higher than the loss modulus G′′, indicating that a stable cross-linked network is formed inside the material and it has a good morphology retention ability.

[0096] 2) Biological significance of low loss factor: A low loss factor indicates that the material is mainly elastic and can maintain a certain synchronous deformation ability during the systolic-diastolic cycle of the heart, which is beneficial to maintaining structural stability after being applied to the dynamic myocardial surface.

[0097] 3) Contribution of dynamic bonds to rheological stability: Although Schiff base bonds are dynamic, under normal physiological conditions, these bonding sites are in dynamic equilibrium, effectively assisting the photocrosslinking network in locking the molecular chain. This multiple crosslinking mechanism indicates that SeGG forms a relatively stable elastic network with good morphology retention, ensuring its long-term stability under complex dynamic mechanical environments in vivo.

[0098] 4. Evaluation of conductivity performance and discussion of conductivity mechanism (1) Construction and conductivity mechanism of GO percolation network: 1) Formation of continuous electronic pathways: Experimental results show that ( Figure 7 The composite hydrogels with different GO contents exhibited different electrical properties. The volume conductivity of the SeGG hydrogel with a final GO concentration of 1.0 mg / mL was approximately 0.041 S / m, indicating that the GO content can regulate the conductivity of the composite hydrogel.

[0099] 2) The role of the π-π conjugated system: Although GO itself has lower conductivity than pure graphene due to its high content of oxygen-containing functional groups, it is highly dispersed in the hydrogel network. Through the interlayer overlap and electrostatic / hydrogen bonding with polymer chains (such as CS and GelMA), it constructs continuous electron transport pathways. In addition, during the crosslinking process, some local areas may form an effective electron tunneling effect through interactions, thereby improving the macroscopic conductivity of the composite material.

[0100] (2) The synergistic assisting effect of SeNPs and polymer chains on charge transport: 1) Coupling of ionic and electronic conductivity: The electrical properties exhibited by the SeGG group are the result of the combined effect of electronic conductivity (provided by GO) and ionic conductivity (provided by the protonated amino group of CS and PBS buffer).

[0101] 2) Contribution of SeNPs: In the SeGG group, OHA-SeNPs, as nanofillers, are distributed between the GO sheets and the polymer matrix. On the one hand, they may act as "relay stations" for charge transport; on the other hand, the dynamic covalent network constructed by OHA and CS locks the distribution position of GO through Schiff base bonds, preventing it from shifting significantly during swelling, thereby ensuring the long-term stability of the conductive pathway.

[0102] (3) Exploration of the compatibility between electrical properties and the physiological environment of the myocardium: 1) Physiological parameter matching: Myocardial tissue has been reported to have certain electrical activity and conductivity characteristics. The 0.041 S / m measured in the SeGG group has a conductivity of approximately 0.02 S / m, which is similar to that of the previously reported myocardial conductive patch. (See the literature "Ding C, Tang G, Sun Y, et al. A functional cardiac patch promotes cardiac repair by modulating the CCR2" for details.) - The paper, titled "cardiac-resident macrophage niche and their cell crosstalk. Cell Rep Med. 2025 Feb 18;6(2):101932. doi: 10.1016 / j.xcrm.2025.101932. Epub 2025 Jan 28. PMID: 39879993; PMCID: PMC11866506," indicates that the material has the potential to simulate the myocardial electrical microenvironment and provide conductive bridging.

[0103] 2) Biological value of electrical signaling: In the infarcted area of ​​myocardial infarction, fibrotic plaques formed by necrotic tissue can block the synchronous conduction of electrical signals, leading to arrhythmias. SeGG stents can assist electrical signals in the damaged area to propagate across the damage interface by providing good conductive bridging.

[0104] 3) Guiding cardiomyocyte maturation: Good electrical conductivity can not only maintain the heart's beating rhythm, but also induce the formation of gap junction proteins (such as Connexin 43) between cardiomyocytes (CMs) at the cellular level, promoting the structural maturation and functional synchronization of cardiomyocytes, which is crucial for functional reconstruction after myocardial infarction.

[0105] Experimental Example 2: Study on the Release Behavior of Drugs in pH / Ultrasound Dual-Response Hydrogels 1. Experimental Methods 1.1 Swelling and In Vitro Degradation Kinetics: The dried SeG, GG, SeGG, and SeGGU hydrogel samples (n=3) were weighed (W0) and then immersed in 10 mL of PBS buffer at pH 7.4 or pH 5.6, respectively, in a 37℃ constant-temperature shaker (50 rpm). Samples were removed at predetermined time points of 0.5, 1, 2, 4, 8, 12, 24, 48, and 72 h, excess surface moisture was blotted with filter paper, and the samples were weighed (Wt). The swelling rate was calculated using the formula "Swelling rate = (Wt-W0) / W0×100%". The samples were then immersed for another 72 h, and after removal at 24, 48, and 72 h, they were freeze-dried and weighed to determine the residual mass (Wd). The degradation behavior was evaluated using the formula "Mass retention rate = Wd / W0×100%".

[0106] 1.2 Study on the environmentally responsive release behavior of nanocomposite hydrogels: The prepared disc-shaped hydrogel samples (8 mm in diameter and 2 mm in thickness) were placed in 10 mL of PBS release medium containing 0.1% (w / v) lysozyme. The following experimental groups (n=3) were set up: Group A (SeGGU): containing OHA-SeNPs / CS / GelMA / GO; Group B (SeGG): same as Group A, serving as the control group without ultrasonic stimulation; Group C (SeG): a physical mixture of selenocysteine ​​and GelMA, serving as the control group without chemical bonding.

[0107] Stimulation response conditions and ultrasound triggering conditions: (1) After the release medium was placed in the hydrogel, the SeGGU group was given low-intensity therapeutic ultrasound stimulation at a preset time point. The ultrasound parameters were set as follows: frequency 1.0 MHz, power density 1.0 W / cm², duration of single treatment 3 min, a total of 14 treatments, with an interval of 24 h between two adjacent treatments, and the temperature of the release medium was controlled; the SeGG group without ultrasound was used as the control. (2) pH gradient setting: In order to evaluate the stability of the material under different pathological microenvironments, the SeGGU samples were set in two parallel experimental groups: acidic environment (pH=5.6) and physiological neutral environment (pH=7.4). All samples were placed in a constant temperature shaker at 37℃ and 50 rpm for sustained release experiment. Short-term detection time points (0.5, 1, 2, 4, 8, 12, 24, 48, 72 h) and long-term detection time points (1, 3, 7, 14, 21, 28 d) were set. At each time point, 1 mL of the release medium was sampled and the same volume of isothermal fresh medium was added to maintain a constant system volume. The concentration of selenium (78Se) in the medium was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the cumulative release rate was calculated.

[0108] 2. Experimental Results 2.1 Analysis of the environmental responsiveness and physicochemical characteristics of hydrogels 2.1.1 pH-induced differential swelling behavior The swelling behavior of each group of hydrogels is shown in the figure. Figure 8 The left figure shows the swelling behavior of SeGGU under different pH conditions. Figure 9 The left image shows that all groups of nanocomposite hydrogels exhibited rapid water absorption after immersion and reached a balanced swelling state within 12 hours. Detailed analysis follows: 1) Dynamic evolution of swelling rate: Under the physiological environment of pH 7.4, SeGGU exhibited a moderate swelling rate (approximately 450%), which indicates that the photocrosslinking network of GelMA and the dynamic covalent network of OHA / CS jointly constructed a stable three-dimensional spatial architecture.

[0109] 2) Acidity Sensitivity Analysis: When the ambient pH decreased to 5.6, the swelling rate of SeGGU significantly increased, with the initial slope of its growth curve being much higher than that of the pH 7.4 group. The molecular mechanism of this phenomenon lies in the significant proton sensitivity of the Schiff base bonds (C=N) present in the hydrogel network. In an acidic microenvironment, protonation leads to partial dissociation of dynamic covalent bonds, thereby reducing the network crosslinking density and inducing permeable expansion of the pore structure. This on-demand swelling characteristic facilitates rapid absorption of tissue exudate in the acidic microenvironment following myocardial infarction (MI) and provides a physical channel for drug diffusion.

[0110] 2.1.2 Acid-triggered programmed degradation behavior Monitoring of the mass retention rate over 72 hours revealed that the SeGGU hydrogel provided by this invention exhibits a precise acid-triggered degradation response. The mass retention rates for each group are shown below. Figure 8 The right figure shows the mass retention rate of SeGGU under different pH conditions. Figure 9 The right image in the middle: 1) Stability Verification: Under simulated normal tissue pH (7.4), SeGGU exhibited strong structural toughness, maintaining a mass retention rate of approximately 60% after 48 hours and retaining its intact morphology after 72 hours. This ensures sufficient structural stability of the material in non-targeted regions, preventing disordered leakage of loads.

[0111] 2) Accelerated degradation kinetics: Under the simulated acidic microenvironment of myocardial infarction zone (pH 5.6), the mass retention rate of SeGGU showed a precipitous drop, falling to about 30% after 48 hours. This confirms that the acidic environment can effectively trigger the overall disintegration of the hydrogel network.

[0112] 3) Technical Advantages: Compared to the slow and linear degradation curve of GG (simply physically encapsulated), the nonlinear and environment-dependent degradation characteristics of SeGGU better meet the clinical needs for intelligent biological scaffolds. This deep coupling between the degradation rate and the infarct microenvironment not only achieves the biodegradability of the material, but also pre-sets a molecular switch for the on-demand release of the carrier SeNPs through the controlled loosening of the network.

[0113] 2.2 Analysis of the environmental responsiveness and physicochemical characteristics of hydrogels 2.2.1 Influence of Components and Physical Fields on Long-Term Release Behavior The cumulative release rates of SeGGU, SeGG, and SeG during the 28-day monitoring period were compared, and the results are as follows ( Figure 10 (Left image in the middle) 1) High-efficiency release performance: SeGGU exhibited a more pronounced ultrasound-enhanced release behavior, with the highest cumulative release rate during the experimental period. The release curve showed a gradual upward trend with ultrasound triggering, indicating that in this system, the migration of OHA-SeNPs not only depends on background degradation but is also regulated by the low-intensity therapeutic ultrasound physical field.

[0114] 2) Differential analysis of the control group: SeGG mainly relies on spontaneous hydrolysis and diffusion release through the gel network when ultrasound stimulation is absent, and the cumulative release rate is lower than that of SeGGU. As a physical mixed selenium source control, SeG, due to the lack of OHA / CS dynamic network and OHA-SeNPs nanostructure, exhibits different release behavior compared to SeGG / SeGGU, demonstrating the regulatory role of composite nanoparticles and dynamic network on the release rhythm.

[0115] 3) Exploration of beneficial effects: The above comparative data confirms that the present invention, by combining the OHA / CS dynamic network with low-intensity therapeutic ultrasound, can achieve exogenously triggered release enhancement while maintaining background release, thereby improving the problem of fixed release rhythm and difficulty in on-demand control of traditional drug-loaded hydrogels.

[0116] 2.2.2 Effect of pH environment on release stability To verify the operational reliability of the hydrogel of this invention under different pH conditions, the release curves of SeGGU at pH 5.6 and pH 7.4 were compared, and the results are shown below. Figure 10 The right image in the middle: 1) pH effect: Experimental results show that an acidic environment can promote the hydrolysis of dynamic Schiff base network and enhance background release; after the application of low-intensity therapeutic ultrasound, SeGGU can still maintain triggerable release enhancement behavior, indicating that the system has both microenvironment response and external ultrasound regulation characteristics.

[0117] 2) Anti-interference demonstration: The results show that the release system constructed in this invention can operate under different pH environments. The acidic environment provides the background release driving force, and the low-intensity therapeutic ultrasound provides the external trigger driving force. Together, they constitute the dual-response regulation mechanism of this invention.

[0118] Experiment Example 3: In vitro cell experiments with hydrogels 1. Experimental Methods 1.1 Extraction and Culture Methods of Primary Cardiomyocytes Hearts were aseptically harvested from 1-3 day old SD rats after sterilization with 75% ethanol. The hearts were then minced in pre-chilled PBS on ice and sequentially digested with trypsin at 4°C and type II collagenase at 37°C. The cell suspension was collected, centrifuged at 1000 rpm for 5 min, and the supernatant was discarded before resuspending the cells. Cardiomyocytes were then purified using differential adhesion: the cell suspension was incubated at 37°C with 5% CO2 for 1.5 h to allow adherence, and non-adherent cells were collected. This differential adhesion process was repeated once. The resulting non-adherent cells were filtered through a 70 μm cell sieve and seeded in high-glucose DMEM medium containing 15% FBS, with BrdU added to inhibit non-cardiomyocyte proliferation. The medium was changed at 48 h and 72 h post-seeding, and after 96 h, primary cardiomyocytes were obtained by culturing in serum-free medium for 10-24 h for subsequent experiments.

[0119] 1.2 Immunofluorescence detection of CX43 and α-actinin in cardiomyocytes of each group Primary cardiomyocytes were seeded in the lower chamber of a 24-well plate or on a glass slide. The hydrogel sample was placed in the upper chamber of a Transwell plate, allowing the cells to primarily receive the effects of the hydrogel release products rather than being directly covered by the hydrogel. The experiment was divided into Control, Hypoxia, Hypoxia-SeG, Hypoxia-GG, Hypoxia-SeGG, and Hypoxia-SeGGU groups. Except for the Control group, hypoxia injury models were established in the other groups. Specifically, cells were cultured in serum-free medium and treated in a hypoxic environment of 1% O2, 5% CO2, and 94% N2 for 24 h to simulate hypoxic injury after myocardial infarction. No glucose-free medium was used during the experiment; therefore, the term "hypoxia model" or "Hypoxia model" was used throughout the text. In the SeGGU group, low-intensity therapeutic ultrasound (1.0 MHz, 1.0 W / cm²) was applied to the hydrogel in the upper chamber of the same Transwell culture system. 2 Cells were subjected to ultrasound treatment for 3 minutes (3 min) in the non-ultrasound group and no ultrasound was applied in the non-ultrasound group. After the intervention, cells in each group were fixed with 4% paraformaldehyde, permeabilized with 0.1% Triton X-100, blocked with 5% BSA, and then incubated with α-actinin and CX43 primary antibody and fluorescent secondary antibody in sequence. The nuclei were stained with DAPI. Finally, images were acquired using confocal microscopy to analyze cell morphology and gap junction protein expression.

[0120] 1.3 Dynamic monitoring of cardiomyocytes loaded on hydrogel scaffolds and their calcium ions After culturing and intervening according to the Transwell system and hypoxia injury model described above, primary cardiomyocytes from each group were harvested for dynamic monitoring of calcium ions. After removing the original culture medium, the cells were gently washed with pre-cooled PBS, followed by the addition of working staining solution containing the Fluo-4 AM probe (final concentration 5 μmol / L), and incubated at 37°C in a 5% CO2 incubator for 45 min in the dark. After incubation, the cells were thoroughly washed with PBS to remove the extracellular free probe, and then real-time dynamic imaging was performed using the time-series module of an inverted laser scanning confocal microscope (model FV3000, Olympus, Japan). The acquired fluorescence video files were imported into ImageJ software for preprocessing, the average fluorescence intensity value of the region of interest (ROI) was extracted, and the data were exported as time-series data.

[0121] 2. Experimental Results 2.1 Immunofluorescence detection of CX43 and α-actinin in cardiomyocytes of each group: Figure 11The results showed that hypoxia treatment disrupted the α-actinin cytoskeleton structure and reduced CX43 expression in primary cardiomyocytes. Treatment with SeG, GG, SeGG, and SeGGU restored α-actinin arrangement and CX43 expression to varying degrees. The SeGGU group showed the most significant improvement in cell structure and connexin expression, suggesting that the release of OHA-SeNPs and the GO conductive network help maintain the structural integrity and electrical coupling basis of cardiomyocytes under hypoxic injury conditions.

[0122] 2.2 Calcium transients in cardiomyocytes ( )monitor: Figure 12 The results showed that the frequency, amplitude and rhythm stability of calcium transients in primary cardiomyocytes were impaired after hypoxia treatment. After treatment with various hydrogels, the SeGGU group showed the most significant recovery of calcium transients, with more stable waveforms and clearer peaks and valleys, indicating that the OHA-SeNPs released by the patch synergistically improved the electrophysiological function of cardiomyocytes after hypoxia injury with the conductive network.

[0123] Experiment Example 4: In vivo animal experiments 1. Experimental Methods 1.1 Construction of a myocardial infarction (MI) model and patch implantation Male SD rats aged 8-10 weeks and weighing 220-250 g were anesthetized and underwent thoracotomy. The left anterior descending coronary artery (LAD) was ligated using 7-0 sutures 1-2 mm distal to the lower border of the left atrial appendage. The infarct model was confirmed when the distal myocardium at the ligation point changed from pink to pale during the procedure. Subsequently, a hydrogel patch was applied flat to the epicardial surface of the infarct area and fixed in place. For the SeGGU group, after the patch was applied and fixed to the cardiac surface, low-intensity therapeutic ultrasound (1.0 MHz, 1.0 W / cm²) was applied to the corresponding area of ​​the patch. 2 (3 min); This step is used to simulate exogenous ultrasound-triggered release after patch implantation, rather than pre-implantation treatment. The sham surgery group only underwent open-chest surgery and did not ligate the LAD.

[0124] 1.2 Echocardiographic assessment of cardiac function One and four weeks post-surgery, rats were anesthetized with isoflurane inhalation, and left ventricular function was assessed using a high-frequency small animal ultrasound system (Vevo 2100). An MS250 probe was used to simultaneously acquire B-mode and M-mode ultrasound images, with a focus on monitoring the motion and morphological changes of the left ventricular anterior wall. Three consecutive stable cardiac cycles were captured to quantitatively measure and compare parameters such as left ventricular end-diastolic diameter (LVIDd), left ventricular end-systolic diameter (LVIDs), ejection fraction (EF), and fractional shortening (FS). Specifically, these parameters included LVEF (%): left ventricular ejection fraction (%), LVFS (%): left ventricular fractional shortening (%), LVIDd (mm): left ventricular end-diastolic diameter (mm), LVIDs (mm): left ventricular end-systolic diameter (mm), ΔEF (%): rate of change in ejection fraction (%), ΔFS (%): rate of change in fractional shortening (%), ΔLVIDd (mm): change in end-diastolic diameter (mm), and ΔLVIDs (mm): change in end-systolic diameter (mm) to assess the recovery of cardiac systolic function.

[0125] 1.3 Histological analysis Four weeks post-surgery, rats were euthanized and their hearts were rapidly removed. After fixation in 4% paraformaldehyde, paraffin embedding, and sectioning, the hearts were stained with hematoxylin and eosin (HE) and Masson's trichrome staining, respectively. HE staining was used to observe myocardial tissue structure; Masson's staining was used to quantify infarct area, calculating infarct size as the percentage of blue staining (collagen fibers) to the left ventricular circumference, and using ImageJ software to measure the thickness of the thinnest part of the infarct wall to assess ventricular remodeling.

[0126] 2. Experimental Results 2.1 Echocardiographic assessment of cardiac function: Figure 13 The results showed that 4 weeks after the operation, LVEF and LVFS were significantly reduced in the MI group, while LVIDd and LVIDs were significantly increased; while cardiac function gradually improved in the SeG, SeGG, and SeGGU groups. Among them, LVEF and LVFS in the SeGGU group recovered to near the level of the Sham group, and ventricular cavity expansion was significantly inhibited, suggesting that its effect on improving cardiac function was relatively optimal.

[0127] 2.2. Histological staining analysis of the heart: Figure 14 HE and Masson staining results showed that the myocardial structure in the MI group was disrupted, while the myocardium in the SeGGU group was well-organized and its structure was restored. Collagen deposition (blue area) was significantly increased in the MI group, and the infarct area was expanded. The SeGGU group had the smallest fibrosis area and the largest infarct wall thickness, suggesting that it can effectively inhibit the process of ventricular remodeling and fibrosis.

[0128] In summary, the SeGGU nanocomposite hydrogel prepared in this invention can achieve a drug delivery mode of "microenvironment-responsive background release - on-demand enhanced release via low-intensity therapeutic ultrasound after patch application". This material supplements selenium-related antioxidant defense, inhibits lipid peroxidation and ferroptosis through OHA-SeNPs, and improves cardiomyocyte electrical coupling and electrical signal conduction in damaged areas through the GO conductive network. Therefore, it meets the repair needs of both anti-ferroptosis protection and electrical microenvironment reconstruction after myocardial infarction, and possesses good application development value.

[0129] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. The application of an ultrasound-responsive conductive composite hydrogel in the preparation of myocardial infarction repair materials, characterized in that, The myocardial infarction repair material includes myocardial patches used to treat myocardial infarction; After the myocardial infarction repair material is applied and fixed to the epicardial surface of the infarct area, low-intensity therapeutic ultrasound is applied to the corresponding area of ​​the myocardial infarction repair material to trigger the on-demand release of selenium nanoparticles modified with oxidized hyaluronic acid in the myocardial infarction repair material; the frequency of the low-intensity therapeutic ultrasound is 1.0-3.0 MHz, the intensity is 0.5-1.5 W / cm², and the single treatment time is 1-5 min; The low-intensity therapeutic ultrasound can be applied directly to the patch area on the heart surface during surgery via a sterile coupling medium, or applied to the corresponding patch area via the precordial surface after surgery. The preparation method of the ultrasonically responsive conductive composite hydrogel includes the following steps: S1. Preparation of selenium nanoparticle dispersion modified with oxidized hyaluronic acid: S11. Dissolve sodium hyaluronate in water, and add sodium periodate solution under light-proof ice bath conditions to carry out an oxidative modification reaction; after the reaction is completed, the resulting reaction solution is dialyzed and dried to obtain oxidized hyaluronic acid with active aldehyde groups. S12. Dissolve oxidized hyaluronic acid in water, add sodium selenite solution, and then add ascorbic acid solution under stirring conditions. Selenium nanoparticles are generated in situ by reduction reaction. After the solution turns orange-red and the color is stable, it is purified by dialysis. The resulting dispersion is the oxidized hyaluronic acid modified selenium nanoparticle dispersion. S2. Dissolve chitosan in 0.5-2 vol% acetic acid solution to prepare a chitosan solution with a mass fraction of 1%-3%. S3. Add methacrylamide gelatin, graphene oxide and photoinitiator to phosphate buffer, disperse evenly and prepare a premix; S4. The oxidized hyaluronic acid-modified selenium nanoparticle dispersion of S1, the chitosan solution of S2, and the premix of S3 are mixed at 4-10℃ under light-protected conditions to obtain a composite bio-ink, which is then printed using digital light processing technology.

2. The application according to claim 1, characterized in that, The molecular weight of the sodium hyaluronate in S11 is 300-500 kDa; the mass ratio of sodium hyaluronate to sodium periodate is 100:10-50.

3. The application according to claim 1, characterized in that, In S11, the oxidation modification reaction takes 2-6 hours.

4. The application according to claim 1, characterized in that, In S12, the ratio of oxidized hyaluronic acid to sodium selenite is 150-250g:1mol, and the molar ratio of ascorbic acid to selenium in sodium selenite is ≥4.

5. The application according to claim 1, characterized in that, The degree of deacetylation of the chitosan in S2 is ≥90%; the substitution rate of the methacrylamide gelatin in S3 is 60%-90%; the monolayer rate of the graphene oxide is >95% and the lateral dimension is 5-8 μm; and the pH of the phosphate buffer is 7.0-7.

5.

6. The application according to claim 1, characterized in that, The photoinitiator described in S3 includes 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylphenylacetone and phenyl-2,4,6-trimethylbenzoylphosphinic acid lithium.

7. The application according to claim 1, characterized in that, In S4, the volume ratio of the hyaluronic acid-modified selenium nanoparticle dispersion, chitosan solution, and premix is ​​2:1:2; the final concentration of the hyaluronic acid-modified selenium nanoparticles is 25-100 μg / mL, calculated as the final composite bio-ink; the final concentration of the photoinitiator is 0.1%-0.5% w / v; the mass-volume concentration of the methacrylamide gelatin is 6%-10%; and the mass-volume concentration of the graphene oxide is 0.5-2.0 mg / mL.

Citation Information

Patent Citations

  • Sequential ultrasonic intervention composite hydrogel and application thereof in preparation of anti-infection-regeneration promoting dressing

    CN120983693A